AT THE WHIM OF NATURE “NATURAL DISASTERS”: CAUSES AND PREVENTION - Pratibha, Akhand; Archna, Akhand (International Journal of Research -GRANTHAALAYAH, 2015)
This paper seeks to determine the natural disasters, causes and effects on environment. Natural disasters are any catastrophic event that is caused by nature or the natural processes of the earth. It could be related to weather, geology, biology or even factors outside the Earth. Examples are earthquakes, hurricanes, droughts and flooding. Nature is bountiful full of resources used by the living organisms use for their survival and well-being. But nature has its own control systems. Resources used up are replenished excesses are checked, all naturally through the biogeochemical cycles, the food chains and webs and other natural phenomena. Thus equilibrium is maintained in nature. This is called ecological balance and has in recent times been disturbed by human activities.G8 Conclusions on Natural Disasters, 1975-2009 to address the increased threats of natural disasters and extreme weather phenomena caused by climate change, such as increased flooding, storm surges, droughts and forest fires, we will act to improve risk preparedness, prevention, monitoring and response times, particularly in developing countries.